Investigating the eastern edge of the kingdom of Aksum: architecture and pottery from Wakarida - Benoist, Anne; Charbonnier, Julien; Gajda, Iwona (Proceedings of the Seminar for Arabian Studies, 2016)
This article presents the results of recent research carried out by the French Archaeological Mission in Wakarida, eastern Tigray, Ethiopia. Excavations revealed a small city dating from the middle and late Aksumite period (AD 350/400–800/850). Despite a relative scarcity of imported items in Wakarida, the local architecture and pottery allowed the team to highlight several parallels with the architecture and pottery collected in the capital, Aksum, suggesting strong elements of cultural unity throughout the Aksumite kingdom.